COX-2 inhibitors and cardiovascular risk - Marwali, Muhammad R.; Mehta, Jawahar L. (Thrombosis and Haemostasis, 2006)
Even though non-steroidal anti-inflammatory drugs (NSAIDs) have been widely used for a long time, the search continues for anti-inflammatory drugs with few side-effects. COX-2 inhibitors are currently most debated, because they have less gastrointestinal side effects but have been linked to increased cardiovascular morbidity and mortality, presumably related to thrombotic events. This has brought about the withdrawal of rofecoxib and other COX-2 inhibitors from the market. Although the results of several large studies with prospective, randomized design and meta-analysis of different trials have led to the demise of many popular COX-2 inhibitors, yet the conclusion seems to be rather simplistic. This review presents evidence from basic biology and clinical studies with the expectation that a balanced position, particularly in relation to increase in cardiovascular events, may be elucidated.
Keywords: Atherosclerosis; thrombosis; inflammation; hypercoagulability; coronary syndrome